Zinc supplementation as an adjunct treatment for acute diarrhea among pediatric patients in developed countries: A meta-analysis - Escueta, Claire Angelica A. (Animo Repository, 2021)
Acute diarrhea is a common childhood illness that remains to be one of the leading causes of morbidity and hospitalization in developed countries. The supplementation of zinc is one of the therapeutic strategies used in treating this diarrheal illness. Currently, evidence on the role of zinc supplementation as a treatment for acute diarrhea in high-income settings needs further evaluation. In view of this, this study aims to determine the effectiveness of zinc supplementation as an adjunct treatment for acute diarrhea among pediatric patients in developed countries.This was conducted in compliance with the PRISMA protocols. Databases of GoogleScholar, PubMed, and ScienceDirect were used for the literature search of randomized controlled trials that were conducted in countries classified under “very high human development” and “high human development” of the UNDP. The RCTs were assessed for bias using the criteria of Cochrane’s collaboration tool. The pooled risk ratio (RR) and mean difference (MD) with a 95% confidence interval (CI) were calculated.A total of four RCTs involving 922 pediatric patients were analyzed. The pooled mean difference (MD) of diarrheal duration among patients who received zinc supplementation versus control is statistically significant (MD: -1.26, 95% CI of -1.95 to -0.56), with a high degree of heterogeneity. The pooled risk ratio (RR) for the presence of acute diarrhea after zinc supplementation for up to three days showed no statistically significant effect (RR: 0.76, 95% CI of 0.41 to 1.40), with a high degree of heterogeneity. The pooled RR for the presence of acute diarrhea after zinc supplementation for four to six days likewise revealed no statistically significant effect (RR: 0.65, 95% CI of 0.27 to 1.58), with a high degree of heterogeneity.This meta-analysis found that zinc supplementation among pediatric patients in developed countries with acute diarrhea has beneficial effects on the reduction of one’s diarrheal duration. Although the risk ratio for the persistence of diarrhea after zinc supplementation showed favorable findings, its wide confidence interval that crosses the line of no effect suggests an inconclusive result.